Ethnic muslims minorities struggle and democratic regime in Myanmar - Md. Mahbubul, Haque; Abdul Majid Hafiz, Mohamed; Mohd Afandi, Salleh (2019)
It is an established perception in Myanmar society that all Muslims are settlers and migrated during the British colonial period. There are a number of distinct Muslim communities in Myanmar, not all of which share the same cultural or ethnic background. It can be categorized into four different groups; Muslims of South Asian origin, Arakan Muslims or Rohingys, Panthays who are ethnically Chinese and Burmese Muslims or Zerabadee. Except Rohingya, rest of the ethnic Muslims are located in urban areas and politically not significant group. The Rohingya minority had strong involvement in the government before and after independence of Myanmar. This is evident in the 2010-2015 parliament, where three Rohingya MPs were elected from the Muslim dominated constituency in Rakhine State. However, the situation changed for all Muslim ethnic minorities after the 2012 Buddhist-Muslim riots. As a result, major political party’s failed to nominate any Muslim candidate in the 2015 general elections. Currently, there is no Muslims representation in Myanmar parliament. This paper argues that, historically Muslims are closer to the national hero Aung San and tried to maintain good ties with the NLD. After the emergence of Buddhist chauvinism in Myanmar, Suu Kyi and her party NLD has been surprisingly silent atrocity against the Muslims. Irrespective of international pressures, the main institutions of the Myanmar government, military, major political parties, media and the radical Buddhist monks targeting and humiliating the Islam and Islamic way of life. One of the main reasons behind is Islamophobia. In this context, it is important to hear the views of Muslim minorities how they coexist in a Myanmar society despite years of hatred and insecurity. Myanmar's ongoing political transition is not merely civilians power sharing with military elites rather accommodating ethnic religious minorities in nation building process.